Monitoring containers : follow the data (O'Reilly Media, 2017)
"Using real-world metrics data from thousands of organizations, Jason Yee explores the latest trends in container adoption and use, shares data on what types of applications organizations are running in containers, and explains how to best monitor these containerized applications."--Resource description page